Marketing Research of Eco-friendly Popularity Factors - Nikolai BELYAEV; Elena TROFIMENKO; Denis STUKALOV; Ilya TSALO (Communications of International Proceedings, 2020)
As the ecological problems are getting worse, the consumers’ thoughts about the environmental protection have led to the diversification in consumer buying approach towards a green lifestyle. Therefore, companies are taking action to develop potential ecological approaches in the green market industry. Green marketing is an evolving concept of marketing that includes issues like eco-friendly products, packaging, labelling, etc. The article focuses on factors that influence consumption of eco-friendly products. Research examines how knowledge about green products of consumers effects the consumption of them. The article analyses thoughts and attitudes of Russian consumers about different characteristics of eco-friendly products, packaging and other. Results of the survey might be used by different organizations: government structures, retailers, producers, marketing agencies and others. Using green marketing concept can help to increase products sales, attractiveness, company’s income and image. For long-term and significant changes in behaviour, it is necessary to develop environmental values through education and support of green markets in the state.
Keywords: Eco-friendly products; environmental marketing; green marketing; customers’ behaviour.